Echocardiographic reference ranges for myocardial work in healthy subjects: A preliminary study. Issue 10 (21st October 2019) - Galli, Elena; John‐Matthwes, Beatrice; Rousseau, Chloé; Schnell, Frederic; Leclercq, Christophe; Donal, Erwan
Abstract: Background: Myocardial work (MW) estimation by pressure‐strain loops (PSL) allows the non‐invasive assessment of myocardial performance. Aim of this study is to provide the reference values for global myocardial work index (WI), constructive work (CW), wasted work (WW), and work efficiency (WE) in a group of healthy volunteers accounting for age and gender. Methods and results: 2D standard and speckle‐tracking echocardiography were performed in 115 healthy volunteers (median age 36.3 [18–69] years, males: 67%). PSLs were used to assess MW. Mean ± standard deviation or median and inter‐quartile range, 5° and 95° percentile values for global myocardial WI, CW, WW, and WE in the whole population were 1926 ± 247 mm Hg, (1534–2356); 2224 ± 229 mm Hg, (1894–2647); 90 (61–123) mm Hg%, (38–195); and 96 (94–97)%, (91–98), respectively. Global WI (2031 ± 247 vs 1874 ± 232 mm Hg%, P = .001) and global CW (2289 ± 261 vs 2194 ± 207 mm Hg%, P = .04) were higher in women than in men. Age did not affect MW parameters. The segmental analysis showed that myocardial WI, CW, and WE were lower in the left ventricular basal segments than in the apex. The apex‐to‐base gradient was inverted for WW (all P < .0001). Conclusions: The assessment of MW is feasible in normal subjects. The presented referral ranges of global myocardial WI, CW, WW, and WE were not affected by age. An apex‐to‐base gradient was observed for all MW parameters. Nevertheless, the wide variability of MW parameters prevents for the moment the application of this technique in the routine clinical setting.